(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
The existing power generation grid with in United States seems to be an antiquated architecture, and the Home Automation is an overhaul that will contain a new features to fit customers’ evolving power demands. Updating a systematic approach like the electricity network has the ability to bring new security vulnerabilities. This article gives an outline of the efforts undertaken in the field of Renewable Energy cyber security. Controller (PCS) Risk, Proposed Smart Stability, Electric Grid Model Based Security, Distributed Generation Data Link Protection, and Smart Grid Simulations for Security Research are really the areas that make up various pieces of the Smart Grid. The Power System is a vast, intricate infrastructure that still needs substantial cyber defense preparation.